Bidirectional communication of the gut-brain axis: new findings in Parkinson’s disease and inflammatory bowel disease - Wanyi, Zhang; Jiao, Yan; Wen, Huang; Bin, Xu; Xuefei, Wang; Lan, Jiang; Liuyin, Zhou (Frontiers in Neurology, 2024)
Parkinson's disease (PD) and inflammatory bowel disease (IBD) are the two chronic inflammatory diseases that are increasingly affecting millions of people worldwide, posing a major challenge to public health. PD and IBD show similarities in epidemiology, genetics, immune response, and gut microbiota. Here, we review the pathophysiology of these two diseases, including genetic factors, immune system imbalance, changes in gut microbial composition, and the effects of microbial metabolites (especially short-chain fatty acids). We elaborate on the gut-brain axis, focusing on role of gut microbiota in the pathogenesis of PD and IBD. In addition, we discuss several therapeutic strategies, including drug therapy, fecal microbiota transplantation, and probiotic supplementation, and their potential benefits in regulating intestinal microecology and relieving disease symptoms. Our analysis will provide a new understanding and scientific basis for the development of more effective therapeutic strategies for these diseases.